Correção laparoscópica de hérnia diafragmática traumática crônica - Domene,Cartas Eduardo (1998)
Diaphragmatic hernia secondary to blunt or penetrating trauma is rarely by itself a fatal event. However, if unpercieved, it may lead to severe complications caused by herniation of abdominal contents to the ethorax. Blunt trauma related to car accidents is the most frequent cause of diaphragmatic hernias. Associated injuries are frequently observed, provoked by severe traumas of great impact. These blunt trauma hernias occur mainly on the left side due to abdominal anatomy, since the liver is usually located on the right side. When injuries are observed on the right they tend to be more severe, generally related to major trauma of solid organs. Less frequently diaphragmatic hernias may be bilateral. The management of diaphragmatic injury would appear to be a simple matter of suturing the defect. However, peroperative diagnosis can be difficult and even at the time of surgery some diaphragmatic injuries can be overlooked if carefull exploration is not done. Associated injuries tend to divert attention from the diaphragmatic injury. Laparoscopic diagnosis and repair have been described with successfull. Laparotomy or thoracotomy can be employed for surgical repair of traumatic diaphragmatic hernias. Standard (laboratory/imaging) examinations may fail to make the diagnosis. Recently, the laparoscopic approach has proved useful for more precise evaluation of such injuries, very often allowing immediate repair of these lesions.